Análise numérica de um sistema integrado coletor solar/armazenador térmico - Santos, Guilherme Henrique Sempionato Souza [UNESP] (2007)
This study shows a numerical analysis of the temperature and speed fields of water during the process of heating through sensible heat in the interior of a cylindric thermal storage, heated laterally and with adiabatics top and base, in order to study the operational conditions of an integrated collector-storage solar water heater (ICSSWH). In a second analysis a model with an internal baffle is created and temperature and velocity fields are analysed. The numerical study is done taking into consideration a bidimensional, transient non linear research in cylindric coordenates, discretized by the technique of finite elements. Its solution is obtained numerically through a computational code developed in a C programming language. The numerical results are validated. A transient analysis of the spped and temperature fields so as of the mixing temperatures and the charging speed, with or without the infernal baffle are carried out taking into account the aim of studying the influence of the so called wall in the free convection of those conditions.